2017
DOI: 10.1080/10717544.2017.1384862
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antitumor effect of gefitinib nanoparticles on human lung cancer

Abstract: Gefitinib (GEF) is the first epidermal growth factor receptor (EGFR)-targeting agent launched as an anticancer drug. It is an accepted opinion that modifying GEF strong hydrophobicity and poor bioavailability would not only enhance its antitumor effects, but also reduce its side effects. In this study, GEF-loadedpoly(e-caprolactone)-poly(ethyleneglycol)-poly(e-caprolactone) (PCEC) -bearing nanoparticles (GEF-NPs) were prepared by a solid dispersion method and characterized. The particle sizes increased with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…In vitro release behavior of PTX and TL from LPNs was explored by placing 1 mL of LPNs in dialysis bags (molecular weight cutoff, 3.5 kDa). 31 The dialysis bags were incubated in 30 mL phosphate buffer (pH, 7.4) containing Tween 80 (0.5%, w/w) at 37°C under gentle shaking (100 rpm). At different time intervals, incubation medium (2 mL) was taken out and replaced by the same volume of fresh preheated medium at specific time points.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro release behavior of PTX and TL from LPNs was explored by placing 1 mL of LPNs in dialysis bags (molecular weight cutoff, 3.5 kDa). 31 The dialysis bags were incubated in 30 mL phosphate buffer (pH, 7.4) containing Tween 80 (0.5%, w/w) at 37°C under gentle shaking (100 rpm). At different time intervals, incubation medium (2 mL) was taken out and replaced by the same volume of fresh preheated medium at specific time points.…”
Section: Methodsmentioning
confidence: 99%
“…In an effort to harness the unique characteristics of nanoparticles for drug delivery, attempts have been made to synthesize gefitinib-loaded nanoparticle constructs (Supplementary Table S1; refs. [29][30][31][32][33][34][35]. Unfortunately, these reports largely focus solely on in vitro cytotoxic effects, without investigation into their therapeutic potential in vivo (29)(30)(31)(32)35).…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of this treatment were also assessed using 18 F-FDG PET/CT imaging. Several studies have shown that 18 F-FDG PET/CT can recognize early decreases in glucose metabolism that are associated with progression-free survival and overall survival in many cancers [25][26][27] . Unlike normal cells, the majority of the energy used by tumor cells relies on glycolysis, mediated by glycometabolic pathways as opposed to aerobic oxidation [28] .…”
Section: Discussionmentioning
confidence: 99%